PAHAM MODERNISASI TERHADAP ASUMSI TEORITIS INDIVIDUALISME DALAM AKUNTANSI SOSIAL - Zulaeha, Sitti; Alimuddin, Alimuddin; Habbe, Abdul Hamid; Mediaty, Mediaty (Bongaya Journal of Research in Accounting (BJRA), 2020)
This article uses a qualitative method, which aims to understand the phenomenon of research subjects by exploring the meaning of individuals or groups on the problem of modernization understanding of the theoretical assumptions of individualism in social accounting. Using the approach of the Hofstede Dimension Paradigm (1980), which identifies "cultural patterns or dimensions that influence people's behavior in significant ways" (Arasaratnam, 2011, p. 45). Several studies have begun to pay attention to the influence of interactions between culture, politics, and the national economy with the process of changing accounting practices in one country. Various studies are trying to uncover the relationship between national culture and organizational culture, with the disclosure of corporate accounting as in Gray, 1988; Perera, 1989; Gibbins et al, 1990 (Sudarwan, 1994). And Hofstede's cultural value dimension is widely used in several fields such as accounting management, auditing, financial accounting, and accounting standards (Noravesh, et al 2007). But, continued Noravesh, et al. (2007), these studies only develop theoretical views and do not develop empirical and systematic research on cultural relations and accounting. So it can be said that there is only the understanding of individualism in social accounting. Because of the culture of a group of people who consider themselves only individualism and not collectivism.